Dancing in the dark: sentiment shocks and economic activity - Boeck, Maximilian; Enders, Zeno; Kleemann, Michael; Müller, Gernot J. (CESifo working papers, 2025)
The business cycle is driven by expectations - some justified, some not - as documented by a host of studies. What is less clear are the conditions that make the economy susceptible to "sentiment shocks." In this paper, we document that uncertainty, as measured by forecaster disagreement, is essential. At times when disagreement is low, sentiment shocks hardly matter for economic activity but are fully absorbed by prices. If, instead, disagreement is high, they move activity with little impact on prices. We obtain these results based on time-series data and a theoretical account based on a New Keynesian model with dispersed information.